Assembly and analysis of the first complete mitochondrial genome of Punica granatum and the gene transfer from chloroplast genome - Lu, Guilong; Zhang, Kai; Que, Youxiong; Li, Yanfeng (Frontiers in Plant Science, 2023)
Pomegranate (Punica granatum L.) is one of the oldest fruits with edible, medicinal and ornamental values. However, there is no report on the mitochondrial genome of pomegranate. In this study, the mitochondrial genome of P. granatum was sequenced, assembled and analyzed in detail, while the chloroplast genome was assembled using the same set of data. The results showed that the P. granatum mitogenome had a multi branched structure, using BGI + Nanopore mixed assembly strategy. The total genome length was 404,807 bp, with the GC content of 46.09%, and there were 37 protein coding genes, 20 tRNA genes and three rRNA genes. In the whole genome, 146 SSRs were identified. Besides, 400 pairs of dispersed repeats were detected, including 179 palindromic, 220 forward and one reverse. In the P. granatum mitochondrial genome, 14 homologous fragments of chloroplast genome were found, accounting for 0.54% of the total length. Phylogenetic analysis showed that among the published mitochondrial genomes of related genera, P. granatum had the closest genetic relationship with Lagerstroemia indica of Lythraceae. The 580 and 432 RNA editing sites were predicted on 37 protein coding genes of mitochondrial genome using BEDTools software and online website PREPACT respectively, but all were from C to U, of which ccmB and nad4 gene were most frequently edited, with 47 sites. This study provides a theoretical basis for understanding the evolution of higher plants, species classification and identification, and will also be useful for further utilization of pomegranate germplasm resources.